2019
DOI: 10.1039/c8ra06662k
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid-loaded starch hemostatic microspheres

Abstract: Efficacious hemostatics have significant potential for use in rapid exsanguinating hemorrhage control by emergency medical technicians or military medics nowadays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…TEG was applied to evaluate and compare the strength of clot which was mixed with sample in vitro. [ 36 ] TEG machine (TEG‐5000, Haemoscope Co., USA) was calibrated by quality control standards at 37 °C before use. 20 µL of CaCl 2 (0.2 mol L −1 ) was added to the TEG cups before adding the blood samples to overcome the anticoagulant effect.…”
Section: Methodsmentioning
confidence: 99%
“…TEG was applied to evaluate and compare the strength of clot which was mixed with sample in vitro. [ 36 ] TEG machine (TEG‐5000, Haemoscope Co., USA) was calibrated by quality control standards at 37 °C before use. 20 µL of CaCl 2 (0.2 mol L −1 ) was added to the TEG cups before adding the blood samples to overcome the anticoagulant effect.…”
Section: Methodsmentioning
confidence: 99%
“…Tranexamic acid-loaded starch microspheres may have potent hemostatic ability from the synergistic role of physical hemostasis by absorption of water to increase endogenous coagulation factors and platelets at the bleeding site and drug hemostasis by effective inhibition of fibrinolysis [180]. The drug-loaded material showed better hemostatic performance (shorter time to complete hemostasis and less bleeding volume) than a commercial hemostat made of microporous polysaccharide hemispheres in rabbit ear artery injury and liver injury, respectively.…”
Section: Flowable Hemostatic Agentsmentioning
confidence: 99%
“…The hemostatic effect of TA has been demonstrated in numerous in vitro, preclinical and clinical studies. 18,[31][32][33] Sarda et al 32 reported on the development of hydroxyapatite with adsorbed TA and demonstrated local hemostatic activity with a lowered aPTT.…”
Section: Uv-vis Absorbance Spectra For Nanoclay Compositions Are Shown Inmentioning
confidence: 99%
“…More recently, Su et al 33 reported on TA loading of starch microspheres and concluded on their potent hemostatic activity with a reduction in aPTT. Our results are in line with these studies and demonstrate that undoped nanoclay microspheres are associated with a reduction in aPTT by half, while TA-doped compositions led to a reduction in aPTT by about two thirds compared to the plasma control alone.…”
Section: Uv-vis Absorbance Spectra For Nanoclay Compositions Are Shown Inmentioning
confidence: 99%